CANTERAS, CUEVAS, ACUEDUCTOS Y CAMINOS CONECTADOS A LA METRÓPOLI WARI - Pérez Calderon, Ismael (2017)
The primary objective of the present research is a description which means in the terms of landscape archeology is done in the direct recognition, complemented with the mapping used in archaeological exploration and sources and sources, arriving at a recorder for the moment 34 archaeological structures Among quarries, caves, aqueducts and roads connected to the Wari metropolis, the indicators that serve to have a main approach and the understanding of the management of the territory in the imperial capital, operation and relation with the peripheral settlements, way of life of The inhabitants, Craft, ceremonial, including the construction of the enigmatic city of stone and the ideology expressed in the cult of the caves, hills, springs and lagoons where the Wamanis or spirits of the Andean cosmovision dwell.